How We Label Students with Disabilities: A Framework of Language Use in an Urban School District in the United States - Back, Lindsey T.; Keys, Christopher B.; McMahon, Susan D.; O'Neill, Kaney (Disability Studies Quarterly, 2016)
Although scientists have often overlooked the role of language used to refer to people with disabilities in their identities, language may reflect societal attitudes that are critical in shaping the experiences of people with disabilities, particularly during formative periods. International controversy surrounds disability-first versus people-first language, but little research to date has explored specific linguistic references to people with disabilities. This study draws on a content analysis of 22 qualitative interviews with students, parents, teachers, and administrators to explore language used to refer to students with disabilities. Results offer the first framework of language in a U.S. urban school district, including people-first, disability-implicit, and disability-first language. Results demonstrate noteworthy variation in form and content, and offer a values-based and contextual understanding of language. This nuanced way of understanding experiences of students with disabilities has implications for potentially improving language used to refer to people with disabilities, as well as creating a more positive disability identity.